Fiscal decentralization and budget control - Von Daniels, Laura; Edward Elgar Publishing (Northampton, Mass. : Edward Elgar Pub., 2016)
How can governments control spending pressure from influential groups, often representing powerful regional interests? This book is concerned with institutional solutions that allow modern nation states to balance historically grown cultural, political and economic diversity. Laura von Daniels combines different literatures in economics and political science, and draws on interviews with former government leaders, and country experts from international organizations. She applies this research to topics such as fiscal institutions and budget balances, presenting a critical review of different institutional approaches to resolving fiscal imbalances and public indebtedness. Students and scholars of various disciplines, including politics, public and social policy, economics and business will find the discussions and detailed description of institutional reforms in emerging market nations to be of use to their research. It will also be of interest to practitioners working on fiscal decentralization and budget control.
1. Fiscal institutions and budget balances -- 2. Overview : institutional approaches to fiscal imbalances and public indebtedness -- 3. Fiscal institutions and their effects on public households -- 4. Fiscal imbalances in Latin American and Caribbean countries -- 5. Fiscal stabilization, subnational fiscal indiscipline and institutional reforms in Brazil -- 6. Fiscal federalism under decentralized budgetary institutions in Argentina -- 7. Comparing institutional reform success in Argentina and Brazil -- 8. Conclusion : balancing subnational fiscal autonomy and overall fiscal stability.
Includes bibliographical references (p. 190-203) and index.
Keywords: Fiscal policy; Intergovernmental fiscal relations; Budget; Finance, Public; Electronic books